Non-emissive RuII Polypyridyl Complexes as Efficient and Selective Photosensitizers for the Photooxidation of Benzylamines - Yagüe, Cristina (2020)
RTI2018-100709-B-C21 CTQ (QMC)-RED2018-102471-T) Junta de Castilla y Leon (BU087G19 FEDER (BU042U16-BU305P18).